Geographic Information System (GIS) for Dengue Research in Indonesia: A Review - Adnanto Wiweko (Tropical Medicine Journal, 2013)
ABSTRACTIntroduction: Geographic information system (GIS) can be very effective tool in combating dengue infection. However, there is only few study that apply GIS in dengue research in IndonesiaObjectives: The purpose of this literature review is to identify how geographic information system (GIS) applications have been used in dengue mapping in Indonesia  and to critically examine the issues, strengths, weakness and challenges inherent to those approaches, especially from  the spatial analysis and public health point of view.Methods: The research articles in English or Indonesian were taken by online only using Google Scholar search engine. Only articles that addressed GIS methodology or dengue–related GIS applications were selected for this review. These articles must contain the combination three words including Geographic Information System (GIS), dengue and Indonesia in its titles or abstracts.Results: Through the review process, conducted in October 2013, it is evident that the applications of GIS in dengue research can be generally categorized into four issues including dengue risk mapping and surveillance (n = 5), combined   remote sensing-GIS (n = 4) web application (n = 2), and climatic and other associated factor with dengue (n = 3). This review explores how GIS approaches have been used to analyze the correlation of dengue incidences with environmental risk factor. GIS also used as a tool to improve dengue surveillance and outbreak management. This review also revealed the lack of GIS techniques using in Indonesian dengue research.Conclusion: GIS-related methodological techniques and tools can be meaning fully applied in dengue research and management.Keywords: Geographic Information System (GIS), dengue, Indonesia